2001
DOI: 10.1021/jf001060r
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spectroscopic Techniques for the Determination of Kjeldahl and Ammoniacal Nitrogen Content of Farmyard Manure

Abstract: The feasibility of determining the nitrogen content of farmyard manure using infrared spectroscopy was investigated. Fifteen samples each of cattle, pig, and turkey manure were analyzed by three infrared techniques: Fourier transform mid-infrared (MIR), using attenuated total reflection (ATR); near-infrared reflectance (NIR-R); and near-infrared optothermal photoacoustic (NIR-OT). The near-infrared measurements were made at wavelengths determined respectively by four (NIR-OT) and five (NIR-R) band-pass filters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…For AN, most previous reports have indicated that the NIRS technique can provide good quantitative predictions ( r c 2 = 0.97, RPD = 5.76 [Malley et al, 2002]; r cv 2 = 0.69, RPD = 1.79 [Saeys et al, 2004]; r c 2 = 0.76, RPD = 2.06 [Saeys et al, 2005b]; r cv 2 = 0.67–0.71, RPD = 1.75–1.91 [Mouazen et al, 2005]; r cv 2 = 0.88–0.92, RPD = 3.75–6.23 [Ye et al, 2005]; RPD = 2.42 [Yang et al, 2006]; RPD = 3.80 [Sørensen et al, 2007]; and r v 2 = 0.88, RPD = 2.62 [Xing et al, 2008]). Kemsley et al (2001) compared three spectroscopic techniques (Fourier transform mid‐infrared spectroscopy [FT‐MIR], NIR optothermal photoacoustic [NIR‐OT], and NIR reflectance [NIR‐R]) for the determination of AN in composted manure samples. Compared with NIR‐OT (coefficient of correlation in calibration [ r c ] = 0.82) and FT‐MIR ( r c = 0.90), NIR‐R had the best performance ( r c = 0.96).…”
Section: Near‐infrared Reflectance Research On the Chemical Compositimentioning
confidence: 99%
“…For AN, most previous reports have indicated that the NIRS technique can provide good quantitative predictions ( r c 2 = 0.97, RPD = 5.76 [Malley et al, 2002]; r cv 2 = 0.69, RPD = 1.79 [Saeys et al, 2004]; r c 2 = 0.76, RPD = 2.06 [Saeys et al, 2005b]; r cv 2 = 0.67–0.71, RPD = 1.75–1.91 [Mouazen et al, 2005]; r cv 2 = 0.88–0.92, RPD = 3.75–6.23 [Ye et al, 2005]; RPD = 2.42 [Yang et al, 2006]; RPD = 3.80 [Sørensen et al, 2007]; and r v 2 = 0.88, RPD = 2.62 [Xing et al, 2008]). Kemsley et al (2001) compared three spectroscopic techniques (Fourier transform mid‐infrared spectroscopy [FT‐MIR], NIR optothermal photoacoustic [NIR‐OT], and NIR reflectance [NIR‐R]) for the determination of AN in composted manure samples. Compared with NIR‐OT (coefficient of correlation in calibration [ r c ] = 0.82) and FT‐MIR ( r c = 0.90), NIR‐R had the best performance ( r c = 0.96).…”
Section: Near‐infrared Reflectance Research On the Chemical Compositimentioning
confidence: 99%
“…Suehara, Nakano, and Yano (2001) and Albrecht et al (2008) obtained r 2 values of 0.95-0.99 for total N and C fractions during the composting process of a predetermined combination of products. FT-NIR spectroscopy also appeared successful for total N in plant residues (Thuriès et al 2007), poultry manure (Reeves 2001), cattle, pig, and turkey manures (Kemsley et al 2001), swine and beef feedlot manures and poultry broiler litter (Millmier et al 2000;Ye et al 2005), and cattle manure (Malley et al 2005). Because the FT-NIR N predictions were less reliable in our study, the BSI/N and Downloaded by [Florida Atlantic University] at 18:10 20 November 2014 Table 3 Performance of FT-NIR calibrations for total C and N and biochemical fractions and the BSI using the partial least squares method and assessment from guidelines proposed by Malley et al (2004) Derivative LIC/N ratios were computed using BSI and LIC as determined by FT-NIR spectroscopy, and total N was quantified by Leco-CNS.…”
Section: Ft-nir Predictions Of Bsi and Licmentioning
confidence: 99%
“…[1][2][3][4] Crop yield and chemical composition are known to be influenced by the uptake and translocation of nitrogen in plant. [5][6][7] Recently, with the analytical methods advances, almost all elements can be detected in plant.…”
Section: Introductionmentioning
confidence: 99%